2017
DOI: 10.1158/0008-5472.can-17-1077
|View full text |Cite
|
Sign up to set email alerts
|

Secretory Autophagy in Cancer-Associated Fibroblasts Promotes Head and Neck Cancer Progression and Offers a Novel Therapeutic Target

Abstract: Despite therapeutic advancements, there has been little change in the survival of patients with head and neck squamous cell carcinoma (HNSCC). Recent results suggest that cancer-associated fibroblasts (CAF) drive progression of this disease. Here, we report that autophagy is upregulated in HNSCC-associated CAFs where it is responsible for key pathogenic contributions in this disease. Autophagy is fundamentally involved in cell degradation, but there is emerging evidence that suggests it is also important for c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
130
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 150 publications
(136 citation statements)
references
References 57 publications
6
130
0
Order By: Relevance
“…CAFs also have a reprogrammed metabolism with high glycolytic flux, autophagy, and senescence, which are cellular processes that provide a nutrient-rich environment for cancer cells (39). Metabolically reprogrammed CAFs have been identified in the tumor stroma of HNSCC and have been shown to promote malignant progression (9,40,41). Here, we demonstrate that CS metabolically reprograms fibroblasts.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…CAFs also have a reprogrammed metabolism with high glycolytic flux, autophagy, and senescence, which are cellular processes that provide a nutrient-rich environment for cancer cells (39). Metabolically reprogrammed CAFs have been identified in the tumor stroma of HNSCC and have been shown to promote malignant progression (9,40,41). Here, we demonstrate that CS metabolically reprograms fibroblasts.…”
Section: Discussionmentioning
confidence: 62%
“…Metabolic compartmentalization with high stromal MCT4 and/or high cancer cell MCT1 and TOMM20, markers of mitochondrial metabolism, occurs in HNSCC (9). Coculture models in vitro and coinjection models in vivo are useful to study the influence of the stroma on carcinoma cells (7,11,41). In breast cancer, a coculture model of fibroblasts and human breast adenocarcinoma cells showed that the lactate released by fibroblasts induces mitochondrial biogenesis in adjacent carcinoma cells (46).…”
Section: Discussionmentioning
confidence: 99%
“…The induction of the self‐renewal potential in these cells indicated a definite CAF‐driven CSC enrichment in these cells. Although studies on interactions between autologous niche‐dysplastic cells are few, niche‐dependent CSC enrichment has been reported to increase malignancy, migration and invasion in breast, hepatic, oral, and pancreatic cancer, with multiple pathways being implicated . Further, Notch1 inhibition could only lead to a minimal effect on CAF‐induced proliferation suggesting the involvement of multiple pathways in the dysplastic cell‐niche cross talk and the redundancy of the Notch1 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, stromal cells, including cancerassociated fibroblasts (CAF), have not yet been studied in ASCC, although CAFs have been reported to play a role in cancer progression in other types of squamous cell carcinoma. 9,10 In this study, we provide the first molecular gene expression profile of targets linked to a panel of targeted therapies in ASCC and demonstrate a central role for the targetable IGF2-PI3K axis, involving tumour cell crosstalk with CAFs.…”
Section: Introductionmentioning
confidence: 90%
“…Nevertheless, all of these analyses have identified PI3K/AKT/mTOR as the pathway most commonly altered in ASCC. Similarly, stromal cells, including cancer‐associated fibroblasts (CAF), have not yet been studied in ASCC, although CAFs have been reported to play a role in cancer progression in other types of squamous cell carcinoma …”
Section: Introductionmentioning
confidence: 99%